Fast Frequency Response of a Doubly-Fed Induction Generator for System Inertia Support - Dejian Yang (Applied Sciences, 2020)
Converter-interfaced doubly-fed induction generators (DFIGs) can provide short-term frequency support (STFS) capability by releasing rotating kinetic energy. After arresting the frequency decrease, the rotor speed should return to its initial operating condition. During the rotor speed recovery process, special attention should paid to the performance of the rotor speed restoration duration and size of the second frequency drop (SFD). This paper suggests an enhanced STFS method of DFIGs to preserve better performance of the frequency nadir with less released rotating kinetic energy and accelerate the rotor speed restoration. To this end, a rotor speed-varying incremental power is proposed and is added to the maximum power tracking (MPT) operation reference during STFS, thereby releasing less rotating kinetic energy from DFIGs; afterward, the power reference smoothly decreases to the reference for MPT operation during the preset period. Test results clearly demonstrate that since even less rotating kinetic energy is utilized, the proposed method can preserve better performance of heightening the frequency nadir; furthermore, the proposed method accelerates the rotor speed restoration when the proposed strategy produces the same SFD as the conventional method, thereby improving the power grid resilience.